Participation in the municipal council for sustainable rural development: Texcoco, State of Mexico - Lucero Pallares, Marcela; Hernández Juárez, Martín; Jiménez Sánchez, Leobardo; Sangerman-Jarquín, Dora Ma.; Jiménez Velázquez, Mercedes; León Merino, Aurelio (Revista Mexicana de Ciencias Agrícolas, 2018)
In the public sector, citizen participation in public decisions tends to be considered in order to improve the quality of public policies, which in turn implies legitimize the State actions. However, "the devil is in the details" and the only indication of this in the regulatory framework is not enough to guarantee an improvement, perhaps the most important challenge lies in its implementation, so that the objective of this research was to determine the scope of citizen participation in the Municipal Council for Sustainable Rural Development, Texcoco, State of Mexico in the period 2009- 2012, identifying the legitimacy of social representatives, the process of communication between social and governmental actors, and the effectiveness of the public action. This research was conducted with a mixed approach, quantitative data were obtained from a survey of 42 stakeholders, and qualitative data were generated with a semi-structured interview, direct observation and document analysis. The results show that, public participation is not effective at all, because of the limits and control exercised by the institutions, making the Council a public space that fulfills the operative and active status, but lack the democratic spirit participatory by not seeking representation of rural society and the productive sectors, and limit the communication process, guiding their purposes, so that the public Council action is not effective to meet the real needs of the rural sector in the municipality.
Keywords: public action; effectiveness; legitimacy; communication process